Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1145/2422.322414
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of Armstrong Relations for Functional Dependencies

Abstract: Abstract. An Armstrong relation for a set of functional dependencies (FDs) is a relation that satisfies each FD implied by the set but no FD that is not implied by it. The structure and size (number of tuples) of Armstrong relatsons are investigated. Upper and lower bounds on the size of minimal-sized Armstrong relations are derived, and upper and lower bounds on the number of distinct entries that must appear m an Armstrong relation are given. It is shown that the time complexity of finding an Armstrong relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 19 publications
3
135
0
5
Order By: Relevance
“…Those well-known concepts in relational database given in this section can be found in [2], [3], [4], [8], [10] and [20]. A relational database system of the scheme R( al, ... ,an) is considered as a table, where columns correspond to the attributes ai's while the row are n-tuples of relation r. Let X and Y be nonempty sets of attributes in R. We say that instance r of R satisfies the FD if two tuples agree on the values in attributes X, they must also agree on the values in attributes Y.…”
Section: Basic Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those well-known concepts in relational database given in this section can be found in [2], [3], [4], [8], [10] and [20]. A relational database system of the scheme R( al, ... ,an) is considered as a table, where columns correspond to the attributes ai's while the row are n-tuples of relation r. Let X and Y be nonempty sets of attributes in R. We say that instance r of R satisfies the FD if two tuples agree on the values in attributes X, they must also agree on the values in attributes Y.…”
Section: Basic Definitionsmentioning
confidence: 99%
“…And the semilattice with greatest elements give an equivalent description of FDs. The closure operations, and other equivalent descriptions of family of FDs have been studied widely by Armstrong [2], Beeri, Dowd, Fagin and Statman [4], Mannila and Raiha [16].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that finding the dependencies from the relation is itself an NP-Complete problem. However, given a set of functional dependencies δ, it can be shown that there always exists a relation on which only those functional dependencies hold; such relations are known as Armstrong relations [3].…”
Section: Bounded Max-arity Reformulation (Bar)mentioning
confidence: 99%
“…, x m ). While constructing an Armstrong relation is exponential in the size of δ, upper and lower bounds on the minimal number of tuples in the relation are known [3]. The BSR problem contrary to BAR refers to a set of dependencies with the specific number of tuples in each projection of the relation on the scope of each dependency of δ.…”
Section: Bounded Size Reformulation (Bsr)mentioning
confidence: 99%
“…A database can be sampled according to many different criteria, such as for example random selection, or selecting data items in such a way that the resulting sample satisfies a set of integrity constraints. Functional dependencies are an example of such integrity constraints, which have been widely investigated in the context of relational databases [3,10,1]. They capture intuitive relationships between data items, and play a central role in the design of databases [16].…”
Section: Introductionmentioning
confidence: 99%